Pemanfaatan Teknologi Web untuk Sistem Absensi di Kantor Desa Kalisusu – Nabire - Arief Rahman Hakim; Nadia Leony L.W (Jurnal Teknologi dan Informatika, 2024)
This study explores the utilization of web technology for the attendance system at Kalisusu Village Office, Nabire, to address the inefficiencies and errors of the manual attendance system. Using the Waterfall method, this study includes needs analysis, system design, implementation, testing, and maintenance. The system was developed using PHP, MySQL, and the Bootstrap framework to create a responsive interface. The results indicate a significant improvement in the efficiency and accuracy of attendance records, with a 75% reduction in data processing time and a 95% increase in recording accuracy compared to the manual system. The main challenge in implementation was user adaptation to the new system, which was overcome through intensive training. This research resulted in a web-based attendance system that not only enhances attendance management at Kalisusu Village Office but also provides a model that can be adapted by other village offices. The broader implications of this research include the potential for improved administrative efficiency and transparency at the village government level.